1995
DOI: 10.1289/ehp.951031150
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy may reduce the return of endogenous lead from bone to the circulation.

Abstract: Hormone replacement therapy (HRT) in postmenopausal women suppresses the increase in bone resorption expected as circulating levels of endogenous estrogen decline. We tested the hypothesis that bone lead content might remain elevated in women on HRT. Fifty six women who at recruitment were on average 35 years postmenopausal were placed on calcium supplementation. Six months later 33 of these women were prescribed either low dose or moderate dose hormone replacement in addition to the calcium supplementation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…HRT is effective in diminishing postmenopausal bone loss and has been considered a cornerstone in preventing osteoporosis. 46 In several prospective trials, HRT increased BMD in older women. [47][48][49][50] Regression analysis revealed that weight was a more important predictor of spine BMD in 1994 and 2000 than exercise habit (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…HRT is effective in diminishing postmenopausal bone loss and has been considered a cornerstone in preventing osteoporosis. 46 In several prospective trials, HRT increased BMD in older women. [47][48][49][50] Regression analysis revealed that weight was a more important predictor of spine BMD in 1994 and 2000 than exercise habit (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A small cross-sectional study of blood lead concentrations among postmenopausal women either on ERT or calcium supplementation found that ERT may reduce the release of lead from bone (Webber et al 1995). However, this was evident only for cortical (tibia) and not trabecular (calcaneus) bone, even though trabecular bone is thought to be more sensitive to estrogen declines than is cortical bone.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of lead in the bone is not necessarily toxic, it can serve as a proxy for lead-induced renal and cardiovascular disease, owing to the steady exposure of target organs to low levels of lead released from bone storage compartment. It is important to recognize that lead may be mobilized from the skeleton during periods of increased bone demineralization, such as pregnancy and lactation [26], very old age [27], and menopause [28], and that during these periods, the risk for HTN may be increased.…”
Section: Measurement Difficultiesmentioning
confidence: 99%